1991
DOI: 10.3168/jds.s0022-0302(91)78632-3
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Genetic Correlations Between Disease and Yield Traits in Dairy Cattle

Abstract: Data included observations on more than 200,000 first lactations of Norwegian cattle. Milk yield, fat and protein percentages, and observations on mastitis, ketosis, and presence of disease (binary coding of 0 or 1) were analyzed. Following Bayesian principles and applying the threshold concept, dispersion parameters for the binary traits (on the underlying scale) with continuous production traits were estimated. Heritabilities were .27, .34, and .43 for milk yield, fat percentage, and protein percentage, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
66
3
3

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(82 citation statements)
references
References 10 publications
10
66
3
3
Order By: Relevance
“…Kelton et al, 1998), the difference was not large compared with the data recorded in a large scale in the United States of America (Zwald et al, 2004a). The estimate of heritability for MAST (0.05) was lower than that found in other studies with a threshold model (Kadarmideen et al, 2000;Heringstad et al, 2005), but consistent with estimates of Simianer et al (1991) and Heringstad et al (2003). Using data from Ontario, Uribe et al (1995) found higher heritabilities for resistance to MAST in the first lactation (0.15); however, when data from all lactations were included, the heritability was not different from 0.…”
Section: Mastsupporting
confidence: 39%
“…Kelton et al, 1998), the difference was not large compared with the data recorded in a large scale in the United States of America (Zwald et al, 2004a). The estimate of heritability for MAST (0.05) was lower than that found in other studies with a threshold model (Kadarmideen et al, 2000;Heringstad et al, 2005), but consistent with estimates of Simianer et al (1991) and Heringstad et al (2003). Using data from Ontario, Uribe et al (1995) found higher heritabilities for resistance to MAST in the first lactation (0.15); however, when data from all lactations were included, the heritability was not different from 0.…”
Section: Mastsupporting
confidence: 39%
“…Among these diseases, clinical mastitis is the most costly disease of the dairy industry [26] due to decreased production, costs of treatment, extra labor, and an increased rate of cow replacement [5]. An antagonistic genetic correlation between milk production and risk of disease showed that the improvement of milk production consequently increased the incidence of clinical mastitis [104,110,112]. augmentation des mammites cliniques chez des vaches laitières à haute production serait causée par une détérioration des mécanismes de défense de la mamelle suite à une hypercétonémie.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the estimated genetic correlations between milk yield and indicators of mastitis suggest that genetic proofs for production traits might be an important source of information for improving an ANN's ability to predict mastitis (Miller 1984;Banos and Shook 1990;Simianer et al 1991;Schutz 1994). Furthermore, SCC itself has a high genetic correlation with mastitis (0.6 to 0.8), indicating that a pattern may exist (Shook and Schutz 1994).…”
Section: Ri =mentioning
confidence: 99%
“…This last point stresses the fact that there are many different variables that influence the occurrence of mastitis. There have been problems associated with statistical modelling of mastitis in the past when all of these factors were either not present or not recorded consistently (Seykora and McDaniel 1986;Rogers et al 1991;Kehrli and Shuster 1994;Schutz 1994;Zhang et al 1994), in addition to the possible limitations of computer power using conventional modelling approaches (Simianer et al 1991;Emanuelson et al 1993).…”
mentioning
confidence: 99%